Pengaruh Beban Kerja Terhadap Stres Kerja Pegawai Sekretariat DPRD Kota Padang - Sherca Marcadia; Lusi Susanti; Ermita, Ermita; Yulianto Santoso (CV. ITTC INDONESIA, 2026)
Work stress is a condition of tension that creates an imbalance between physical, cognitive, affective, behavioral, and psychological symptoms, which affect the emotions, thought processes, and condition of an employee/staff member. Workload is a number of activities or tasks that must be completed by a worker within a certain period, which in its implementation requires the capability of an individual. This study aims to examine the effect of Workload (variable X) on Work Stress (variable Y). The population in this study includes all employees at the Secretariat of the Regional House of Representatives of Padang City, totaling 111 people. The sample in this study consists of 87 people using Cochran's formula with a confidence level of 95%. The technique for determining the sample in each stratum is the Proportionate Stratified Random Sampling technique. The research results indicate that there is a significant influence of workload on job stress of employees at the Secretariat of the Regional People's Representative Council (DPRD) of Padang City, with a significance value of 0.000 < 0.05 and t count = 6.521 > t table 1.662 as well as the regression coefficient value of 0.471, so it can be concluded that there is a significant influence of the Workload variable (X) on the Job Stress variable (Y).